2018
DOI: 10.1371/journal.pone.0209316
|View full text |Cite
|
Sign up to set email alerts
|

The influence of subanaesthetic ketamine on regional cerebral blood flow in healthy dogs measured with 99mTc-HMPAO SPECT

Abstract: Subanaesthetic ketamine has recently been proven to be a highly effective and fast acting alternative treatment for several psychiatric disorders. The mechanisms responsible for ketamine’s antidepressant effects remain unclear, but a possible explanation could be that ketamine interacts with regional cerebral blood flow (rCBF). Therefore, the effects of two subanaesthetic ketamine doses on rCBF were evaluated. Twelve dogs were randomly assigned to one of the three treatment conditions (condition saline, condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Brain imaging studies have reported similar abnormalities in regional cerebral blood flow of certain brain regions in dogs with pathological anxiety and in humans suffering from depression and anxiety disorders [17][18][19][20][21][22][23]. Furthermore, altered perfusion of these brain regions following intravenous subanesthetic ketamine administration has been demonstrated both in humans and dogs [24][25][26][27][28][29][30]. Additionally, functional imaging studies have demonstrated altered function of the serotonergic system in several cortical brain regions, both in humans and dogs suffering from mood and anxiety disorders [31][32][33].…”
Section: Introductionmentioning
confidence: 84%
“…Brain imaging studies have reported similar abnormalities in regional cerebral blood flow of certain brain regions in dogs with pathological anxiety and in humans suffering from depression and anxiety disorders [17][18][19][20][21][22][23]. Furthermore, altered perfusion of these brain regions following intravenous subanesthetic ketamine administration has been demonstrated both in humans and dogs [24][25][26][27][28][29][30]. Additionally, functional imaging studies have demonstrated altered function of the serotonergic system in several cortical brain regions, both in humans and dogs suffering from mood and anxiety disorders [31][32][33].…”
Section: Introductionmentioning
confidence: 84%